POLA INVESTASI TENAGA KERJA WANITA INDONESIA DI DESA SIKANCO KECAMATAN NUSAWUNGU KABUPATEN CILACAP - Siti Ma’sumah (El-Jizya: Jurnal Ekonomi Islam, 2019)
Islam teaches that husbands are obliged to provide for their families. But not a few women are just working after they get married to help the family's economy. Family background that is not capable of causing people not to have higher education. Low education makes people work in the informal sector with relatively low salaries. The low salary received is not enough to meet daily needs, especially the needs of clothing and shelter. This shortage triggered the wives to work abroad with high salaries even though they worked in the informal sector. This study aims to describe the investment pattern of Indonesian female workers in Sikanco Village, Nusawungu, Cilacap District.